Actual problems of legal regulation and legislation in the sphere of physical culture and sports in Ukraine - Marina Sannikova (Kharkiv State Academy of Physical Culture, 2019)
Purpose: identify current issues of legal regulation and legislation in the sphere of physical culture and sports in Ukraine. Material & Methods: the method of theoretical analysis and systematization of literary sources on the topic of research allowed to find out the problematic field of legal regulation of the sphere of physical culture and sports in Ukraine. The analysis of documentary materials allowed to characterize the structure of the system of legal regulation in the sphere of physical culture and sports. The method of historicism made it possible to identify the objective features of sports law, as a new branch of the legal system of Ukraine. The application of the method of analogy of the studied laws and system analysis allowed us to determine the general trends in the development of sports law. The method of mathematical modeling made it possible to develop a special algorithm for analyzing the effectiveness of professional activities of specialists in the field of sports law. Results: determined the structure of the system of legal regulation in the sphere of physical culture and sports; clarified the objective features of sports law, as a new branch of the legal system of Ukraine; established general trends that significantly affect the development of sports law and the most significant shortcomings in the legal regulation of the sphere of physical culture and sports in Ukraine. Conclusions: it was found that the rapid development of sports necessitates the improvement and codification of the legislation governing sports relations in Ukraine. It has been established that for the establishment and future development of sports law, as an integrated branch in the legal system of Ukraine, we need highly qualified specialists, who are well oriented in the field of physical culture and sports.